Vocational quidance in the context of basic training youth to agricultural activity in the „school – university” - PONOMARENKO, Oksana (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
Well planned and well organized career guidance services are increasingly important to improve career guidance for young people. The process of training the qualified specialists is one of the main problems of the professional-practical education. So the above-mentioned problem in the article is considered the major among the problems which the high and secondary school meets.